The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11616-022-00762-8
|View full text |Cite
|
Sign up to set email alerts
|

Female chatbots are helpful, male chatbots are competent?

Abstract: Chatbots have in recent years increasingly been used by organizations to interact with their customers. Interestingly, most of these chatbots are gendered as female, displaying stereotypical notions in their avatars, profile pictures and language. Considering the harmful effects associated with gender-based stereotyping at a societal level—and in particular the detrimental effects to women—it is crucial to understand the effects of such stereotyping when transferred and perpetuated by chatbots. The current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Regarding the entrusted tasks to the synthetic voices, outcomes revealed that the HQ voice gendered as female was considered as better suited than the HQ male voice and both the LQ voices (female and male, respectively), in achieving front office and healthcare tasks. With regard to housework, a typical gender stereotype seems evident, according to which female-gendered CAs are considered more suitable for nurturing and caring occupations, while CAs gendered as male are preferred for those tasks requiring authority, competence, and agency [37,38]. Supporting this speculation is the fact that both HQ and LQ female voices were found to be better suited to perform household tasks than HQ and LQ male voices.…”
Section: High Quality Female Voice High Quality Male Voice Low Qualit...mentioning
confidence: 98%
“…Regarding the entrusted tasks to the synthetic voices, outcomes revealed that the HQ voice gendered as female was considered as better suited than the HQ male voice and both the LQ voices (female and male, respectively), in achieving front office and healthcare tasks. With regard to housework, a typical gender stereotype seems evident, according to which female-gendered CAs are considered more suitable for nurturing and caring occupations, while CAs gendered as male are preferred for those tasks requiring authority, competence, and agency [37,38]. Supporting this speculation is the fact that both HQ and LQ female voices were found to be better suited to perform household tasks than HQ and LQ male voices.…”
Section: High Quality Female Voice High Quality Male Voice Low Qualit...mentioning
confidence: 98%
“…The issue of stereotyping has mixed academic evidence. For example, Bastiansen et al (2022) deployed the Stereotype Content Model to research the effects of warmth and gender of a chatbot on stereotypes, trustworthiness, aid, and capability. They find no divergent outcomes stemming from exposure to heat and assigned gender.…”
Section: Potential Risks Of Implementing Ai Chatbots In Heismentioning
confidence: 99%
“…In this regard, an impactful effect is users' perception of gender in a CA (Gong, 2008), which is caused by the combination of several cues (i.e., name, avatar, and description) (Bastiansen et al, 2022;Feine et al, 2020). Thereby, gender can be defined as a non-essential category which is repeatedly performed based on societal norms (Morgenroth & Ryan, 2018).…”
Section: Introductionmentioning
confidence: 99%